Flame-retardant cellulose composite film and preparation method thereof

Through the winding and addition of carbon dots between titanate nanofibers and nanocellulose, an organic-inorganic interpenetrating network structure is formed, which solves the problem of high cellulose combustion and achieves flame retardant fibers with high mechanical properties and excellent flame retardant properties. Plastic composite membrane.

CN119463308APending Publication Date: 2025-02-18CENTRAL SOUTH UNIVERSITY OF FORESTRY AND TECHNOLOGY

Patent Information

Application Number
CN202411482789.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, cellulose has a low limit oxygen index (LOI), high combustion, and there is a fire hazard, and traditional flame retardants have problems of environmental pollution and poor material compatibility.

Method used

By winding the titanate nanofibers and nanocellulose, an organic-inorganic interpenetrating network structure is formed, and carbon dots and crosslinking agents are added to prepare a flame-retardant cellulose composite membrane.

Benefits of technology

It significantly improves the mechanical properties of the composite membrane and has excellent flame retardant, smoke suppression and heat insulation properties. At the same time, the use of flame retardant is reduced, ensuring high synergy of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463308A_ABST
    Figure CN119463308A_ABST
Patent Text Reader

Abstract

The invention relates to a flame-retardant cellulose composite film and a preparation method thereof, belongs to the field of flame-retardant materials, and aims to solve the problems that a cellulose film is inflammable, poor in compatibility with an inorganic flame retardant, relatively low in mechanical property and the like. The main components of the composite membrane comprise nanocellulose, titanate nanofibers, carbon dots and a cross-linking agent. The preparation method comprises the following steps: firstly, enabling the carbon dots to react with the nanocellulose under the action of an initiator; secondly, adding titanate nanofibers into the carbon dot modified nanocellulose suspension, and uniformly mixing; then, adding a cross-linking agent and uniformly dispersing to obtain a mixed solution; and finally, casting the solution into a culture dish, and curing in a vacuum drying oven to prepare the flame-retardant cellulose composite film. According to the preparation method, the compatibility of the flame retardant and the nano cellulose is remarkably improved, the mechanical property is enhanced, and the composite film has excellent flame retardance, smoke suppression and heat insulation characteristics and is suitable for preparing the flame-retardant cellulose composite film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of flame retardant materials, and in particular to a flame retardant cellulose composite film and a preparation method thereof. Background Art

[0002] Cellulose is widely used in many fields, including food packaging, biomedicine, flexible electronic devices and aerospace interiors, due to its excellent renewability and biodegradability. In addition, cellulose has the advantages of high specific surface area, good lightweight properties, excellent biocompatibility and easy surface functionalization. However, the limiting oxygen index (LOI) of cellulose is only 25.2%, and its flammability is high, which leads to fire hazards during transportation, storage and use, greatly limiting its further application.

[0003] In the prior art, the flame retardancy of cellulose is usually improved by adding flame retardants. Traditional halogen flame retardants will generate a lot of heat and toxic hydrogen halide gas when burned, causing serious environmental pollution. Although inorganic flame retardants are non-toxic, they are often poorly compatible with cellulose matrix materials due to the large amount of addition, and will cause the mechanical properties of the material to deteriorate.

[0004] Therefore, developing a flame-retardant cellulose composite film with low additive amount, good compatibility with the matrix material, and improved mechanical properties has become an urgent problem to be solved. Summary of the invention

[0005] The present invention aims to solve the deficiencies in the prior art and provide a flame retardant cellulose composite film and a preparation method thereof. The present invention forms an organic-inorganic interpenetrating network structure by entanglement of titanate nanofibers and nanocellulose. Compared with traditional nanocellulose, the composite film has significantly enhanced mechanical properties and has excellent flame retardancy, smoke suppression and heat insulation properties.

[0006] To achieve the above object, the present invention proposes a flame retardant cellulose composite film, the components of which include nanocellulose, titanate nanofibers, carbon dots and a crosslinking agent. The mass percentages of the components are as follows: nanocellulose accounts for 82.0% to 83.1%, titanate nanofibers account for 0.9% to 2.1%, carbon dots account for 2.0%, and the rest is a crosslinking agent.

[0007] Furthermore, the nanocellulose used is derived from bleached wood pulp, which is oxidized, homogenized and purified to obtain a nanocellulose suspension.

[0008] Furthermore, the physical form of the titanate nanofibers is changed by a hydrothermal reaction to obtain fibrous titanate.

[0009] Furthermore, the carbon dots are polyamino carbon-based nanomaterials prepared from ginkgo leaves and ethylenediamine as raw materials, and have a size of about 4 nm.

[0010] Furthermore, the cross-linking agent is epichlorohydrin.

[0011] Furthermore, the preparation method of the titanate nanofiber is:

[0012] S1. Titanium oxysulfide powder, distilled water and sodium hydroxide solution were mixed evenly in a mass ratio of 2:15:37.2, and then added into a polytetrafluoroethylene reactor. The mixture was sealed in a forced air drying oven for reaction at a temperature of 200°C for 48 hours and a sodium hydroxide solution concentration of 15 mg / L. A titanate suspension was obtained after the reaction was completed.

[0013] S2. The prepared titanate suspension is washed, filtered and dried to obtain titanate nanofibers.

[0014] Furthermore, the preparation method of the carbon dots is:

[0015] S1. After washing the ginkgo leaves with distilled water, put them into a forced air drying oven for drying at a temperature of 60° C. for a drying time of 24 to 48 hours. After being completely dried, grind them into powder to obtain pretreated ginkgo leaf powder.

[0016] S2. After mixing ginkgo leaf powder, ethylenediamine and deionized water in a mass ratio of 1:5.4:100, transfer to a polytetrafluoroethylene reactor, seal it, put it in a forced air drying oven, and react at 200°C for 8 hours to obtain a brown-yellow solution.

[0017] S3. The obtained brown-yellow solution is centrifuged and purified by dialysis. The dialysis time is 24 h to 48 h to obtain the final carbon dot solution.

[0018] The present invention further provides a method for preparing the flame-retardant cellulose composite film, the specific steps of which are as follows:

[0019] Step 1: Under the action of an initiator, the carbon dots react with the nanocellulose suspension, and the nanocellulose suspension modified by carbon dots is obtained by purification through dialysis.

[0020] Step 2: Add the titanate nanofibers to the carbon dot-modified nanocellulose suspension, and continue stirring until uniformly dispersed to obtain a carbon dot-modified nanocellulose suspension cross-linked with the titanate nanofibers.

[0021] Step 3: Add epichlorohydrin to the above solution and stir rapidly until it is evenly dispersed to obtain a mixed solution.

[0022] Step 4: Cast the mixed solution into a culture dish and place it in a vacuum drying oven for curing to finally obtain a flame retardant cellulose composite film.

[0023] Further, in step 1, the concentration of the carbon dot solution is 0.5wt%. The preparation method of the carbon dot-modified nanocellulose suspension is as follows: carbon dots are introduced into the nanocellulose suspension, and after uniform mixing, N-(3-dimethylaminopropyl)-N'ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added in sequence in a mass ratio of 0.8:30:0.09:0.34, and magnetic stirring is performed at 150rpm for 12h at room temperature, and the dialysis time is 36h to 48h to obtain a carbon dot-modified nanocellulose suspension.

[0024] Further, in step 2, the mass ratio of the titanate nanofibers to the carbon dot-modified nanocellulose suspension is (0.32-0.78):30.8, and the mixture is stirred at 150 rpm for 1 hour at room temperature.

[0025] Further, in step 3, the mass ratio of epichlorohydrin and the carbon dot-modified nanocellulose suspension cross-linked with titanate nanofibers is 5:(31.12-31.58), and stirring is carried out at 150 rpm for 10 min at room temperature.

[0026] Furthermore, in step 4, the curing temperature is 55° C., the curing time is 10 h, and the pressure is 0.08 to 0.085 MPa.

[0027] The present invention has at least the following beneficial effects:

[0028] 1. The carbon dot solution of the present invention is simple to prepare, and is prepared by mixing ginkgo leaves with ethylenediamine and then using a hydrothermal method. Ginkgo leaves, as a carbon source, are biomass waste, and can achieve waste recycling, which has the advantage of resource conservation.

[0029] 2. The present invention prepares a flame-retardant cellulose composite film with excellent mechanical properties by mixing carbon dots, nanocellulose, titanate nanofibers and a crosslinking agent. The introduction of carbon dots changes the negative charge on the surface of nanocellulose to positive charge, enhances the entanglement with titanate nanofibers, and significantly improves the interfacial compatibility between the titanate flame retardant and the cellulose matrix, thereby improving the overall mechanical strength of the material.

[0030] 3. The flame-retardant cellulose composite film prepared by the present invention also has significant flame retardant properties and smoke suppression effects. The addition of titanate nanofibers accelerates the thermal degradation of nanocellulose and promotes the formation of a dense carbon layer. The carbon layer can effectively block the penetration of heat and oxygen, delay the release of toxic and combustible gases, and achieve the dual effects of flame retardancy and smoke suppression.

[0031] 4. The flame-retardant cellulose composite film of the present invention also exhibits good thermal insulation performance. Its unique organic-inorganic interpenetrating network structure has a high porosity, which can significantly reduce heat radiation and enhance heat reflection effect, while effectively preventing heat conduction and improving the thermal insulation capacity of the cellulose matrix.

[0032] 5. The present invention reduces the amount of flame retardant used by optimizing the formula, and at the same time forms a good synergistic effect between nanocellulose, carbon dots and flame retardant. Even in the case of low flame retardant addition, it can still maintain excellent flame retardant performance, while ensuring smoke suppression performance, heat insulation performance and mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the preparation method of the flame retardant cellulose composite film of the present invention;

[0034] Figure 2 This is a transmission electron microscopy image of the carbon dots prepared in Example 1;

[0035] Figure 3 This is a scanning electron microscope image of the titanate nanofiber prepared in Example 1;

[0036] Figure 4 The stress-strain curves of the films obtained in Examples 1 to 4 of the present invention and Comparative Examples 1 to 2;

[0037] Figure 5 The stress-strain curves of the films obtained in Example 2 of the present invention and Comparative Examples 3 to 4;

[0038] Figure 6 This is a digital photo of the nanocellulose film prepared in Comparative Example 1 during vertical combustion;

[0039] Figure 7 This is a digital photo of the carbon dot-nanocellulose composite film prepared in Comparative Example 2 during vertical combustion;

[0040] Figure 8 This is a digital photo of the flame-retardant cellulose composite film prepared in Example 2 when it is burning vertically;

[0041] Fig. 9 The thermal decomposition temperature curves of the films obtained in Example 2 of the present invention and Comparative Examples 1-2; DETAILED DESCRIPTION

[0042] The present invention is described in detail below with reference to the embodiments.

[0043] Embodiment 1

[0044] See also Figure 1 The present invention provides a technical solution, comprising the following steps:

[0045] S1. Disperse 1 g of ginkgo leaf powder in 100 g of distilled water, add 5.4 g of ethylenediamine, mix evenly on a magnetic stirrer at 150 rpm, transfer to a polytetrafluoroethylene reactor, and react in a blast drying oven at 200° C. for 8 hours. After the reaction is completed, the resulting brown-yellow solution is centrifuged and dialyzed for 24 to 48 hours to obtain a purified carbon dot solution.

[0046] S2. 0.8 g of the carbon dot solution was added to 30 g of the nanocellulose suspension, and 0.09 g of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 0.34 g of N-hydroxysuccinimide were added in sequence, stirred on a magnetic stirrer at 150 rpm at room temperature for 12 hours, and then dialyzed for 36 to 48 hours to obtain a carbon dot-modified nanocellulose suspension.

[0047] S3. 4 g of titanium oxysulfide powder was dissolved in 30 g of distilled water, and then 74.4 g of 15 mg / L sodium hydroxide solution was added, mixed evenly on a magnetic stirrer at 150 rpm, and then transferred into a polytetrafluoroethylene reactor and reacted in a blast drying oven at 200° C. for 48 hours. After the reaction was completed, the obtained suspension was washed, filtered and dried to obtain titanate nanofiber powder.

[0048] S4. 0.32 g of the titanate nanofiber powder prepared in S3 was added to 30.8 g of the carbon dot-modified nanocellulose suspension obtained in S2, and magnetically stirred at 150 rpm for 1 hour at room temperature. Then, 5 g of epichlorohydrin was added, and stirring was continued on a magnetic stirrer at 150 rpm for 10 minutes to obtain a mixed solution. The mixed solution was cast in a culture dish, and then the culture dish was transferred to a vacuum drying oven at 55°C for curing for 10 hours to obtain a flame-retardant cellulose composite film.

[0049] The transmission electron microscopy image of the carbon dots with polyamino characteristics prepared in this example is as follows: Figure 2 As shown, it can be seen that the carbon dots are spherical and have a size of 4 nm.

[0050] The scanning electron microscope image of the titanate nanofibers prepared in this example is as follows: Figure 3 As shown, it can be seen that the physical form of titanate changes after the hydrothermal reaction and becomes fibrous.

[0051] Embodiment 2

[0052] The preparation method of Example 1 was followed, except that the mass of the titanate nanofiber powder in S4 was changed to 0.47 g.

[0053] Embodiment 3

[0054] The preparation method of Example 1 was followed, except that the mass of the titanate nanofiber powder in S4 was changed to 0.62 g.

[0055] Embodiment 4

[0056] The preparation method of Example 1 was followed, except that the mass of the titanate nanofiber powder in S4 was changed to 0.78 g.

[0057] Comparative Example 1

[0058] 30 g of nanocellulose suspension was mixed with 5 g of epichlorohydrin and stirred at room temperature with a magnetic stirrer at 150 rpm for 1 hour until the mixture was uniform. Subsequently, the resulting mixed solution was evenly cast in a culture dish, and the culture dish was transferred to a vacuum drying oven at 55°C for curing for 10 hours to finally obtain a nanocellulose film.

[0059] Comparative Example 2

[0060] 30.8 g of the carbon dot-modified nanocellulose suspension prepared in Example 1 S2 was mixed with 5 g of epichlorohydrin and stirred at room temperature with a magnetic stirrer at 150 rpm for 1 hour until the mixture was uniformly mixed. Subsequently, the resulting mixed solution was uniformly cast in a culture dish, and the culture dish was placed in a vacuum drying oven at 55° C. for curing for 10 hours, and finally a carbon dot-nanocellulose composite film was obtained.

[0061] Comparative Example 3

[0062] The only difference between this comparative example and Example 2 is that the titanate nanofibers used in S4 of Example 2 are replaced by non-fibrous titanate purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The remaining steps are the same as those of Example 1 and will not be repeated here.

[0063] Comparative Example 4

[0064] The only difference between this comparative example and Example 2 is that the carbon dots used in Example 2 S2 are replaced by carbon dots with patent application number CN202110801305.2, and the remaining steps are consistent with Example 1 and will not be repeated here.

[0065] The films obtained in Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to stress-strain tests. The results are as follows: Figure 4 As shown. Figure 4It can be seen that the average tensile strength and elongation at break of the film with added titanate nanofibers (Examples 1 to 4) are significantly improved compared to the film without added titanate nanofibers (Comparative Examples 1 to 2). This is due to the presence of multiple forces such as electrostatic attraction and hydrogen bonds between nanocellulose, carbon dots and titanate nanofibers, which effectively improve the mechanical strength of the film. During the experiment, it was found that when the amount of titanate nanofibers added was too much, the mechanical properties would be affected. It has been verified that when the amount of titanate nanofibers added was 0.47g (Example 2), the film exhibited the best average tensile strength and elongation at break.

[0066] To further verify the material properties, the film showing the best mechanical properties (Example 2) and Comparative Examples 3-4 were subjected to stress-strain tests. The results are as follows: Figure 5 As shown. Figure 5 It can be clearly seen that the film of Example 2 has significant advantages in average tensile strength and elongation at break. These results show that the fibrous titanate and polyamino carbon dots prepared in the present invention not only effectively enhance the mechanical properties of the film, but also have more prominent advantages compared to other types of materials.

[0067] The LOI values ​​of the films obtained in Example 2 and Comparative Examples 1 to 3 were tested and the flame retardant levels were evaluated, and the test results are shown in Table 1. The LOI value of the flame-retardant cellulose composite film with the addition of titanate nanofibers (Example 2) is significantly higher than the LOI value of the film without the addition of titanate nanofibers (Comparative Examples 1 to 2), which shows that the addition of titanate nanofibers is beneficial to improving the flame retardant properties of the film, and when the addition amount of titanate nanofibers is 0.47g, the LOI value of the obtained film (Example 2) reaches 56.5%, which is 55.4% higher than that of the nanocellulose film, and has an excellent flame retardant effect. At the same time, when the addition amount of the two titanates is 0.47g (Example 2 and Comparative Example 3), the film prepared by fibrous titanate (Example 2) has a significantly higher LOI value, which confirms the advantageous role of fibrous titanate in the flame-retardant cellulose composite film of the present invention. This is because the physical entanglement between titanate and the matrix material when it is in fibrous form is much higher than that in non-fibrous form. The prepared film has a tighter network structure and higher porosity, which increases heat reflection and O2 flow during combustion and accelerates thermal degradation. Figures 6 to 8 As shown, the films obtained in Example 2 and Comparative Examples 1-2 were ignited twice respectively, and the films obtained in Comparative Examples 1-2 could not extinguish themselves once ignited and did not have a flame retardant grade. However, the film obtained in Example 2 had a flame retardant effect and reached the V-0 grade.

[0068] The limiting oxygen index (LOI) values ​​of the films obtained in Example 2 and Comparative Examples 1 to 3 were tested, and their flame retardant levels were evaluated. The test results are shown in Table 1. The results show that the LOI value of the flame-retardant cellulose composite film (Example 2) with the addition of titanate nanofibers is significantly improved compared with the film (Comparative Examples 1 to 2) without the addition of titanate nanofibers, indicating that the addition of titanate nanofibers helps to improve the flame retardant properties of the film. Among them, when the addition amount of titanate nanofibers is 0.47g, the LOI value of the obtained film (Example 2) reaches 56.5%, which is 55.4% higher than that of the nanocellulose film, showing an excellent flame retardant effect.

[0069] At the same time, when the addition amount of titanate is 0.47g (Example 2 and Comparative Example 3), the film prepared by fibrous titanate (Example 2) shows a higher LOI value, which further confirms the superior role of fibrous titanate in flame-retardant cellulose composite film. This phenomenon can be attributed to the significant enhancement of the physical entanglement between fibrous titanate and the matrix material, which makes the film form a tighter network structure and has a higher porosity, thereby increasing the heat reflection effect and reducing the circulation of oxygen during the combustion process, accelerating the thermal degradation process.

[0070] like Figures 6 to 8 As shown, two ignition tests were conducted on the films obtained in Example 2 and Comparative Examples 1-2. The results showed that the films obtained in Comparative Examples 1-2 could not extinguish themselves once ignited and did not reach the flame retardant level. However, the film prepared in Example 2 showed a significant flame retardant effect and reached the V-0 level, further proving the advantages of the present invention in improving the flame retardant properties of the film.

[0071] Table 1

[0072]

[0073] The flame retardant cellulose composite film (Example 2) which has shown the best flame retardant effect and the films obtained in Comparative Examples 1-2 were subjected to thermogravimetric analysis. The thermal decomposition temperature curves are shown in FIG. Figure 8 As shown. Fig. 9 It can be clearly observed that the thermal decomposition temperature of the flame-retardant cellulose composite film prepared in Example 2 is significantly increased, indicating that the film after adding titanate nanofibers has better heat resistance, which is much better than the film without adding titanate nanofibers (Comparative Examples 1-2). In addition, the final carbon residue of the film with added titanate nanofibers (Example 2) is also significantly higher than the film obtained in Comparative Examples 1-2, which further proves the key role of titanate nanofibers in improving the heat resistance and flame retardancy of the film.

[0074] The flame retardant cellulose composite film (Example 2) showing the best flame retardant effect and the films obtained in Comparative Examples 1 to 2 were subjected to cone calorimetry tests, and the test results are summarized in Table 2. It can be clearly seen from Table 2 that the heat release rate (HRR), total heat release rate (THR), smoke production rate (SPR), total smoke production rate (TSP), carbon monoxide generation (COP) and carbon dioxide generation (CO2P) of the film (Example 2) with the addition of fibrous titanate nanofibers are significantly reduced compared to the film (Comparative Examples 1 to 2) without the addition of titanate nanofibers. This is because titanate nanofibers can accelerate the formation of a dense carbon layer, effectively inhibit heat loss during combustion, and reduce heat transfer and the release of smoke and toxic gases. In addition, the reduction in carbon dioxide generation (CO2P) not only responds to the national dual-carbon policy, but also improves the utilization rate of biomass waste-Ginkgo biloba.

[0075] Table 2

[0076]

[0077] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention, rather than to limit it. Those skilled in the art may still modify or replace the technical solution of the present invention without departing from the claims of the present invention, and such modifications or replacements shall be deemed to fall within the protection scope of the present invention.

Claims

1. A flame retardant cellulose composite film, characterized in that: The composite membrane is composed of nanocellulose, titanate nanofibers, carbon dots and a crosslinking agent, wherein the mass percentages of the components are as follows: 82.0% to 83.1% of the nanocellulose, 0.9% to 2.1% of the titanate nanofibers, 2.0% of the carbon dots and the remainder of the crosslinking agent.

2. The flame-retardant cellulose composite film according to claim 1, characterized in that: The titanate nanofiber is obtained by changing the physical form through a hydrothermal reaction and is in a fiber shape.

3. The flame-retardant cellulose composite film according to claim 1, characterized in that: The carbon dots are polyamino carbon-based nanomaterials prepared from ginkgo leaves and ethylenediamine as raw materials, and have a size of about 4 nm.

4. The flame-retardant cellulose composite film according to claim 1 or 3, characterized in that: The method for preparing the carbon dots comprises the following steps: S1. Wash the ginkgo leaves with distilled water and dry them in a forced air drying oven at a drying temperature of 60° C. for 24 to 48 hours. After drying, grind them into powder to obtain pretreated ginkgo leaf powder. S2. Ginkgo leaf powder, ethylenediamine and deionized water were mixed in a mass ratio of 1:5.4:100 and added into a polytetrafluoroethylene reactor. The mixture was reacted at 200° C. in a forced air drying oven for 8 h to obtain a brown-yellow solution. S3. Centrifuge the brown-yellow solution and dialyze for 24 h to 48 h to obtain a purified carbon dot solution.

5. The method for preparing a flame-retardant cellulose composite film according to claim 1, characterized in that: The specific steps include: Step 1: reacting the carbon dots with the nanocellulose suspension under initiator conditions, and purifying by dialysis to obtain the carbon dots-modified nanocellulose suspension; Step 2: adding titanate nanofibers to the carbon dot-modified nanocellulose suspension, stirring until uniformly dispersed, to obtain a carbon dot-modified nanocellulose suspension cross-linked with titanate nanofibers; Step 3: Add epichlorohydrin to the nanocellulose suspension of the carbon dots modified by cross-linking the titanate nanofibers, and stir quickly until uniformly dispersed to obtain a mixed solution; Step 4: Cast the mixed solution into a culture dish, transfer it into a vacuum drying oven for curing, and obtain a flame-retardant cellulose composite film.

Citation Information

Patent Citations

  • Method for preparing multicolor fluorescent carbon dots, fluorescent carbon dots prepared by method and application of fluorescent carbon dots

    CN114045170A

Cited By

  • Anti-dripping flame-retardant film and manufacturing method thereof

    CN122167953A

  • Preparation method of fire-retardant and ultraviolet-resistant bifunctional cellulose film

    CN122749965A